Análise dimensional da aresta lateral de corte e núcleo de instrumentos reciprocantes antes e após o preparo do canal radicular - Sampaio , Felipe Cavalcanti (2016)
Objective: The purpose of the present study was to analyze the influence of flute and shank dimensions present at the first 4mm to occurrence of plastic deformations and dimensional alterations in reciprocating instruments after RCP. Methodology: The reciprocating instruments used were Reciproc® R25, R40 and R50, WaveOne® Small, Primary and Large, Unicone® #20, #25 and #40. Scanning electron microscopy images were obtained of the first 4mm from the instrument’s tip (30X magnification) before and after shaping of simulated curved root canals. The instruments were used only once. The images were transferred to software AxioVision® to measure the instruments: flute area (µm2), shank area (µm2), flute longitudinal length (µm) and instrument transversal diameter (µm). The difference of data before and after root canal preparation (RCP) was compared by Students’ T test for paired samples and differences between instruments of similar sizes was performed by ANOVA followed by Tukey’s test. The instruments were classified for the plastic deformations presence after RCP. Results: Reciproc® instruments showed larger flutes and smaller shanks. The Reciproc® R40 showed significant difference for transversal diameter at 0.5mm from the tip. Reciproc® had no plastic deformations. Unicone® instruments showed significant differences on #20 instruments for transversal diameter at 1.5 and 3.0mm from the tip, and instrument #25 had difference at 1.5 and 3.0mm and second and third flute longitudinal length. Plastic deformations were visualized on one instrument #20m and on three #40. WaveOne® instruments showed significant differences for first and fourth flutes length of WaveOne® Primary, and tranversal diameter at 2.0mm from the tip of WaveOne® Large. Plastic deformations were present in two of three Large instruments. Conclusions: In summary, Reciproc® instruments had greater area and length of flutes and smaller shanks compared to Unicone® and WaveOne® of similar sizes. Reciproc® showed greater flute to shank ratio. WaveOne® had the lowest flute to shank ratio. Unicone® instruments showed more plastic deformations. Higher flutes and lesser shanks had less plastic deformations after curved RCP.